Stosowanie kar pieniężnych z tytułu naruszenia ustawy antymonopolowej – praktyka i postulaty de lege ferenda - Kołnierzak, Lucyna (Kwartalnik Prawa Publicznego, 2012)
This article discusses the problem of imposing fines for breaches of the provisions of Act of 16 February 2007 on Competition and Consumer Protection. Pursuant to Title VII of that Act the President of the Office of Competition and Consumer Protection may impose upon the undertaking fines by way of a decision. When fixing the amount of the fines the duration, gravity and circumstances of the infringement of the provisions of the Act, as well as the previous infringement should be particularly taken into account. Special kind of fines are fines imposed, if the undertaking, even if unintentionally had implemented a concentration without a consent of the President of the Office of Competition and Consumer Protection. Author suggests that imposed fines may be too low in relation to the gravity of the infringement.